2003
DOI: 10.1128/aem.69.6.3192-3202.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Ecology in Commercial Sauerkraut Fermentations

Abstract: Knowledge of bacteriophage ecology in vegetable fermentations is essential for developing phage control strategies for consistent and high quality of fermented vegetable products. The ecology of phages infecting lactic acid bacteria (LAB) in commercial sauerkraut fermentations was investigated. Brine samples were taken from four commercial sauerkraut fermentation tanks over a 60-or 100-day period in 2000 and 2001. A total of 171 phage isolates, including at least 26 distinct phages, were obtained. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 28 publications
5
88
1
Order By: Relevance
“…The results are in concordance with an earlier study wherein the phages of Pseudomonas were successfully isolated only from water samples, while in soil and feces no Pseudomonas specific phages were detected (22).Earlier studies attribute similar results to relatively low viable counts of phage capable of infecting specific bacteria (6), relatively low rates of phage diffusion within soil, particularly under drier conditions (18) and relatively high rates of free-phage inactivation within soil (27). There have been a number of reports of phage presence, in various environments (14,2).…”
Section: Discussionsupporting
confidence: 82%
“…The results are in concordance with an earlier study wherein the phages of Pseudomonas were successfully isolated only from water samples, while in soil and feces no Pseudomonas specific phages were detected (22).Earlier studies attribute similar results to relatively low viable counts of phage capable of infecting specific bacteria (6), relatively low rates of phage diffusion within soil, particularly under drier conditions (18) and relatively high rates of free-phage inactivation within soil (27). There have been a number of reports of phage presence, in various environments (14,2).…”
Section: Discussionsupporting
confidence: 82%
“…Phages probably pass gastro-intestinal tract safely because they are able to survive in an acidic environment, however, pH = 6 to 7 is the optimum range for most of them to show the highest efficiency. Lu et al (2003) reported that 24 phage isolates were obtained in fermentation tanks with sauerkraut (pH < 3.5) after 60 days. Yan et al (2012) reported that growing pigs fed diets supplemented with anti-Salmonella bacteriophage had greater digestibility of DM, which is in agreement with our results (Experiment 1, phase 3).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of starter cultures may improve the food shelf-life by inhibition of spoilage microorganisms based on nutrient competition (Fernandez-Díez et al, 1985;Garrido-Fernandez et al, 1997;Duran Quintana et al, 1999;Holzapfel, 2002;Devlieghere et al, 2004;Silvestri et al, 2009), and should improve aroma and flavor of final products not only by inhibition of the spoilage microorganisms that interfere with the process of aroma generation, but also directly through their metabolism (Aponte et al, 2010). Until now, Lactobacillus plantarum (Lu et al, 2003) and Lactobacillus pentosus (Rodríguez-Gomez et al, 2013) have been the primary LAB species commonly applied to produce fermented table olives (Hurtado et al, 2012). However, some yeasts, such as Wickerhamomyces anomalus, Saccharomyces cerevisiae and Pichia membranifaciens have been selected as starters for this kind of production (Garrido-Fernandez et al, 1997;Bautista-Gallego et al, 2011;Arroyo-Lopez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%